The Role of Exosome-miRNA as Biomarkers of Alzheimer’s Disease: A Systematic Review of Case-Control and Longitudinal Studies. - Zhou, Haiqing; Liu, Ying; Li, Kaijun; Mou, Shangdong; Cao, Xia; Chen, Qingjuan (Actas Espanolas de Psiquiatria, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder, and its diagnosis remains challenging. Exosomal microRNAs (miRNAs), due to their stability, tissue specificity, and ability to cross the blood–brain barrier, show significant promise as ideal biomarkers for AD. The present study aimed to systematically elucidate the relationship between the exosomal miRNA expression changes and AD pathogenesis (including Aβ deposition, Tau protein phosphorylation, and neuroinflammation) and to evaluate their potential utility in clinical screening and therapeutic interventions. A systematic literature search was conducted in the PubMed and Web of Science databases to identify human case–control or cohort studies reporting expressions of mature exosomal miRNAs in the serum, plasma, cerebrospinal fluid, saliva, or central nervous system cells. After evaluating the quality of the studies using the National Institutes of Health quality assessment tool, the identified differentially expressed miRNAs were summarized and functionally integrated. Among the 390 screened records, 48 studies (n = 3046 AD patients) met the inclusion criteria. The analysis identified 120 exosomal miRNAs that are differentially expressed at different AD ages. Six miRNAs (miR-125b, miR-146a, miR-193b, miR185-5p, miR-29b/c, miR-21-5p) were most consistently reported and showed significant correlation with AD pathology.